THE EFFECT OF DIFFERENT SHADE LEVELS ON THE RESULTS OF Stenotaphrum secundatum GRASS ON MEDITETTANEAN SOIL - I.M.B., Sembiring; Witariadi, N. M.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
Forage is a very important requirement for ruminants. One of the grasses that has high adaptation to the influence of shading levels is Stenotaphrum secundatum grass. This study aims to determine the effect of different shade levels on the yield of Stenotaphrum secundatum grass on Mediterranean soil. The research was conducted in Sading Village, Mengwi District, Badung Regency. The study lasted for 12 weeks, using a completely randomized design (CRD). There were 4 treatments and each treatment was repeated 7 times, thus consisting of 28 experimental units. The treatments were: N0: 0% no shade, N1: 20% shade level, N2: 40% shade level, N3: 60% shade level. Variables observed were leaf dry weight, stem dry weight, total forage dry weight, root dry weight, ratio of leaf dry weight to stem dry weight, and ratio of total forage dry weight to root dry weight. The results showed that the effect of different shade levels on Stenotaphrum secundatum grass gave significant results on the variables of leaf dry weight, stem dry weight, total forage dry weight, root dry weight and ratio of total forage dry weight to root dry weight, while the variable ratio of leaf dry weight to stem dry weight gave nonsignificant results. It can be concluded that different shade levels affect the yield of Stenotaphrum secundatum grass on Mediterranean soil and 20% shade level gives the best Stenotaphrum secundatum grass yield on Mediterranean soil.